Association between recent internal travel and malaria in Ugandan highland and highland fringe areas. Issue 6 (17th March 2015) - Lynch, Caroline A.; Bruce, Jane; Bhasin, Amit; Roper, Cally; Cox, Jonathan; Abeku, Tarekegn A.
Abstract Objective To examine the association between travel (recency of travel, transmission intensity at destination compared to origin and duration of travel) and confirmed malaria in Uganda. Methods Health facility‐based case–control study in highland (~2200 m), and highland fringe (~1500 m) areas with adjustment for other covariates. Results In the highland site, patients who had travelled to areas of higher transmission intensity than their home (origin) areas recently were nearly seven times more likely to have confirmed malaria than those who had not (OR 6.9; P = 0.01, 95% CI: 1.4–33.1). In the highland fringe site, there was also a statistically significant association between travel and malaria (OR 2.1; P = 0.04, 95% CI: 1.1–3.9). Conclusions For highland areas, or areas of low malaria transmission, health authorities need to consider internal migrants when designing malaria control programs. Control interventions should include information campaigns reminding residents in these areas of the risk of malaria infection through travel and to provide additional mosquito nets for migrants to use during travel. Health authorities may wish to improve diagnosis in health facilities in highland areas by adding travel history to malaria case definitions. Where routine monitoring data are used to evaluate the impact of interventions on the malaria burden in highland areas, health authorities and donors need ensure that only cases from the local area and not 'imported cases' are counted.